The Influence of Giving Tempe Flour Toward the Amount and Morphology of White Male Rat (Rattus norvegicus) Erythrocytes Wistar Strain was Affected by Cigarette Smoke - I Made Subhawa Harsa (Berkala Kedokteran, 2019)
Abstract: Cigarette smoke was one of free radicals source for the body. Free radical contain in cigarette smoke were hydroxide radicals (•OH). Hydroxide radicals would cause erythrocytes damage. Antioxidants were substances that can prevent free radicals. Now, natural antioxidants source has developed, one of that is tempe, because of it contained antioxidants substances such as carotene, Vitamin E, isoflavon, and factor II antioxidants. This resource was for knowing the influence of giving tempe flour toward the amount and morphology of white male rat (Rattus norvegicus) erythrocytes wistar strain was affected by cigarette smoke. A pure experiment which was used the post test only-control group design method. Sample of the resource was white male rat wistar strain aged of 3-4 month as much 30 rats by the weight around 180-220 gram. The samples divided into 3 groups that were control group (K1), treatment group 1 (K2), and treatment group 2 (K3), each group consists of 10 rats. Control group was not given a special treatment, it only got a standard feed, treatment group 1 got special treatment and it was affected by cigarette smoke, furthermore, treatment group 2 got standard feed, it was affected by cigarette smoke and tempe. Analysis of data used one way anova experiment. The test showed the significance P-value = 0,036 that was <α (0,05). The result showed that there was the influence of giving tempe flour toward the amount and morphology of white male rat (Rattus norvegicus) erythrocytes wistar strain was affected by cigarette smoke. Keywords: cigarette smoke, free radicals, erythrocytes, antioxidants, tempe